Mathematical Thinking Styles of Students with Academic Talent - Reyes-Santander, Pamela (2018)
This study explores the predominant mathematical thinking style that students with academic talent used in solving mathematical problems. Thinking styles are preferences by subjects in the way of expressing mathematical skills against a task, in this case, visual, formal and integrated. We assessed 99 students from an academic support talent program, in a retrospective ex post facto study with only one group. We administered the questionnaire mathematical thinking styles of Borromeo-Ferri and determined that these students exhibited mostly an integrated style of thinking, which involves the use of symbols and verbal representations with visual expressions in solving mathematical exercises. They also show a strong orientation to address the problems of combined mode, which involves considering them as a whole at a time.